1999
DOI: 10.1103/physrevb.59.9771
|View full text |Cite
|
Sign up to set email alerts
|

Surface sensitivity of impurity incorporation: Mg at GaN (0001) surfaces

Abstract: The interplay of surface termination, reconstruction patterns, and availability of species involved determines the incorporation of impurities during growth. We study ab initio this interplay for Mg at the GaN ͑0001͒ surfaces and find that optimal incorporation conditions strongly depend upon surface orientation and cannot be predicted using bulk stoichiometric arguments. With reasonable assumptions on the kinetics, high densities of Mg can be achieved in the absence of hydrogen and the Ga surface displays sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 33 publications
2
45
0
Order By: Relevance
“…Our studies of bulk samples from two opposite sides, e.g. grown with N and Ga-polarity, do not indicate substantial difference in Mg incorporation for different growth polarities as predicted theoretically [12] and observed in MBE grown samples [13], where up to 30 times more Mg was incorporated in Ga-polarity, as determined by secondary ion mass spectrometry. The last authors [13] also indicated accumulation of Mg on the sample surface which would be consistent with our results.…”
mentioning
confidence: 62%
“…Our studies of bulk samples from two opposite sides, e.g. grown with N and Ga-polarity, do not indicate substantial difference in Mg incorporation for different growth polarities as predicted theoretically [12] and observed in MBE grown samples [13], where up to 30 times more Mg was incorporated in Ga-polarity, as determined by secondary ion mass spectrometry. The last authors [13] also indicated accumulation of Mg on the sample surface which would be consistent with our results.…”
mentioning
confidence: 62%
“…The surface polarity dependence of Mg incorporation has already been investigated, both theoretically and experimentally. For instance, Bungaro et al [21] have demonstrated by ab initio calculations that the Ga surface displayed superior Mg incorporation characteristics with respect to the N surface. This conclusion has been also deduced from several SIMS studies [22,23].…”
Section: Mg Incorporation Behaviourmentioning
confidence: 98%
“…We believe that the presence of the Mg allows the surface to satisfy electron counting, leading to completely filled or completely empty surface state bands, for structures containing either 1/4 ML [19] or 3/4 ML [18] of Mg substituting for Ga. Qualitatively, one expects such a surface to be non-reactive, and have relatively low diffusion barriers compared to the bare GaN surface. Hence, a surfactant effect (smooth, 2-D growth) could be expected, although more detailed computations are required to confirm this expectation.…”
Section: Indium-covered Surfacesmentioning
confidence: 99%